Potential impacts of climate change in the United States - USA. Congressional Budget Office (Washington, DC, 2009)
"This paper summarizes the current state of scientific understanding of the potential effects of projected changes in climate and related developments. The paper describes the wide range of potential impacts, including changes in: seasonal weather patterns; the amount and type of precipitation; storms and sea level; regular climate fluctuations; ocean acidity; ecosystems and biodiversity; agriculture, forestry, and fishing; water supply and other infrastructure; and human health. The discussion focuses mainly on projections of impacts in the United States but also refers to impacts elsewhere that could be particularly severe and could indirectly affect the United States. The paper draws from various primary and secondary sources, particularly the Fourth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC), a major national assessment recently released by the National Science and Technology Council in the Executive Office of the President, and a number of surveys published by the U.S. Climate Change Science Program, which integrates executive-branch research on climate and global change."